Bis(silanetellurone) with C-H center dot center dot center dot Te Interaction - Ghosh, Moushakhi; Panwaria, Prakash; Tothadi, Srinu; Das, Aloke; Khan, Shabana (Inorganic Chemistry, 2020)
Herein, we report the synthesis of a series of bis(silanechalcogenones) [Ch = Te (2), S (3), or Se (4)] using an N-heterocyclic silylene-based SiCSi pincer ligand (1). 2 is the first example of a bis(silanetellurone) derivative. The bonding patterns of 2-4 were extensively studied by natural bond orbital, quantum theory of atoms in molecules, and noncovalent interaction index analyses, and these exhibit weak C-H center dot center dot center dot Ch interaction. The analogous reaction of 1 with trimethyl N-oxide produced a novel bis(cyclosiloxane) derivative (5). All of the complexes are duly characterized by single-crystal X-ray diffraction studies, multinuclear nuclear magnetic resonance (H-1, C-13, and Si-29) spectroscopy, and high-resolution mass spectrometry.